1955
DOI: 10.1021/ja01608a038
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Colchicide1 (Demethoxycolchicine)

Abstract: Dehydrobromination of 7-Keto-8-bromocholesteryl Acetate (IX).-A solution of 1 g. of IX and 30 cc. of pyridine was refluxed for 7 hours and the reaction mixture was treated in the usual manner; the reddish-brown oily product was chromatographed through a column of 50 g. of alumina (Brockmann Grade II) with a petroleum ether-benzene (1:1) solution (200 cc.). The eluate was fractionated into 40 cc. each.Fractions 3 and 4 afforded a solid which after crystallization from alcohol gave 80 mg. of colorless crystals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1962
1962
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The product was purified by radial chromatography (95:5 CH2Cl2-MeOH) and was obtained as a yellow solid in a yield of 49%. Compound 14: mp 109-110 °C; [a]26D -179°(c 0.9); NMR 7.31 (d, 1 H, H-12, J = 9.9 Hz), 7.29 (s, 1 , H-8), 7.16 (d, 1 H, H-ll, J = 9.8 Hz), 6.90 (br, 1 , NH), 6.51 (s, 1 , H-4), 4.62 (p, 1 , H-7), 3.93 (s, 3 H, 3-OCH3), 3.90 (s, 3 H, 2-OCH3), 3.67 (s, 3 H, l-OCH3), 2.68 [m, 2 H, 10-CH2 (CH2)2CH3], 2.48 (m, 2 , H-5), 2.22 (m, 1 , H-6), 1.99 (s, 3 H, COCH3), 1.80 (m, 1 , H-6), 10-Isobutyl-l0-demethoxycolchicine (15). This compound was synthesized as described above using isobutylmagnesium bromide, and the reaction was monitored by TLC using 95:5 CH2Cl2-MeOH.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The product was purified by radial chromatography (95:5 CH2Cl2-MeOH) and was obtained as a yellow solid in a yield of 49%. Compound 14: mp 109-110 °C; [a]26D -179°(c 0.9); NMR 7.31 (d, 1 H, H-12, J = 9.9 Hz), 7.29 (s, 1 , H-8), 7.16 (d, 1 H, H-ll, J = 9.8 Hz), 6.90 (br, 1 , NH), 6.51 (s, 1 , H-4), 4.62 (p, 1 , H-7), 3.93 (s, 3 H, 3-OCH3), 3.90 (s, 3 H, 2-OCH3), 3.67 (s, 3 H, l-OCH3), 2.68 [m, 2 H, 10-CH2 (CH2)2CH3], 2.48 (m, 2 , H-5), 2.22 (m, 1 , H-6), 1.99 (s, 3 H, COCH3), 1.80 (m, 1 , H-6), 10-Isobutyl-l0-demethoxycolchicine (15). This compound was synthesized as described above using isobutylmagnesium bromide, and the reaction was monitored by TLC using 95:5 CH2Cl2-MeOH.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts to hydrolyze 9demethoxy-9-tosylisocolchicine with 5% NaOH in water/ ethanol also resulted in ring contraction product as well as colchiceine. We have found that when the alkoxymagnesium compound is the nucleophile rather than the 7.9 13.2 (±1.7) 53.7 (±2.5) CH3 (10) 4.1 56.6 (±1.5) 96.7 (±9.9) CH2CH3 (11) 4.2 54.9 (±6.8) 96.5 (±9.4) CH2CH2CH3 (12) 3.5 41.7 (±1.5) 89.2 (±5.9) CH(CH3)2 (13) 4.2 44.9 (±5.4) 90.0 (±1.9) (CH2)3CH3 ( 14) 26 13.9 (±7.0) 24.7 (±5.8) CH2CH(CH3)2 (15) 8.5 13.4 (±1.9) 36.7 (±4.6) CH(CH2CH3)(CH3) (16) 10 19.6 (±5.7)…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Another simple analogue of colchicine is colchicide ( 193 ), in which the C-10 methoxy group is replaced by a hydrogen atom. This compound ( 193 ) is accessible from thiocolchicine ( 6 ) by reaction with Raney nickel in acetone (Scheme ).…”
Section: Miscellaneous Modification Of Rings a B And C: Organometalli...mentioning
confidence: 99%
“…The more easily desulfurized 1,8-p-menthylene sulfone (XXXVIII) reacted in accordance with Bonner's findings (73) with complete inversion, which the author explains by assuming a Raney nickel desulfurization was also used in work on the chemistry of colchicine. Demethoxycolchicine (XLa) was obtained in 61% yield from thiocolchicine (XLb) by treatment with Raney nickel deactivated by boiling acetone (373), whereas hexahydrodemethoxycolchicine (XLI) was obtained in yields up to 40% when active nickel was used (373,452). The compound XLII was also desulfurized without hydrogenation of the aromatic ring (451).…”
Section: Sulfides and Disulfidesmentioning
confidence: 99%